2016
DOI: 10.1007/s12291-016-0554-0
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Reductase C677T Polymorphism and Recurrent Pregnancy Loss Risk in Asian Population: A Meta-analysis

Abstract: The C677T polymorphism of the methylenetetrahydrofolate reductase (MTHFR) gene was implicated to be associated with thrombophilia due to its role in catalyzing the formation of 5-methylenetetrahydrofolate, a co-substrate for the conversion of homocysteine to methionine. Several case-control studies were investigated MTHFR C677T polymorphism as risk for recurrent pregnancy loss (RPL). These studies rendered contradictory results, some indicating that the polymorphism is associated with the risk of RPL whereas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 73 publications
2
23
0
Order By: Relevance
“…To our knowledge, this is the first study to provide evidence linking 3′-UTR polymorphisms of MTHFR with RPL. Combined with previous findings linking MTHFR polymorphisms with increased RPL susceptibility [ 15 16 17 ], our data implicate genetic variation in the 3′-UTR, further supporting the role of MTHFR in RPL.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To our knowledge, this is the first study to provide evidence linking 3′-UTR polymorphisms of MTHFR with RPL. Combined with previous findings linking MTHFR polymorphisms with increased RPL susceptibility [ 15 16 17 ], our data implicate genetic variation in the 3′-UTR, further supporting the role of MTHFR in RPL.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have reported haplotype analysis of MTHFR 677C>T and 1298A>C [ 6 11 12 14 16 17 ], but the single nucleotide polymorphisms (SNPs) present in the 3′-UTR have not been analyzed. These additional SNPs may alter MTHFR expression or function, as was found with MTHFR 677C>T SNPs with regard to RPL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from several meta-analyses that have examined the possibility of an association between MTHFR polymorphisms and the risk of RPL are variable ( 29 30 31 32 33 34 35 36 37 ). Data from a recent, large meta-analysis indicated that maternal and paternal MTHFR C677T and A1298C polymorphisms were associated with RPL.…”
Section: Discussionmentioning
confidence: 99%
“…It is a homologous  Building a molecular typing protocol for rs1801133 based on real-time PCR HRM technique form of the cysteine amino acid but differs from the -CH2 moiety [6]. High levels of homocysteine in the blood are often associated with increased cardiovascular risk, neurological diseases, miscarriage, cancer, infertility in different populations and races [7][8][9][10][11]. In addition, this SNP is associated with the prognosis of treatment with anticancer drugs.…”
Section: Introduction Ethylenetetrahydrofolate Reductase (Mthfr)mentioning
confidence: 99%